2022
DOI: 10.1029/2021ja030143
|View full text |Cite
|
Sign up to set email alerts
|

On the Applicability of Single‐Spacecraft Interferometry Methods Using Electric Field Probes

Abstract: When analyzing plasma waves, a key parameter to determine is the phase velocity. It enables us to, for example, compute wavelengths, wave potentials, and determine the energy of resonant particles. The phase velocity of a wave, observed by a single spacecraft equipped with electric field probes, can be determined using interferometry techniques. While several methods have been developed to do this, they have not been documented in detail. In this study, we use an analytical model to analyze and compare three i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…The use of the time delay between V 1 and − V 2 provides the speed estimate of only a few km/s, but these voltage signals were poorly correlated, and the solitary wave was barely propagating along this antenna ( L 12 ≈ − 0.01), which makes the speed estimate highly uncertain (Wang et al., 2021). The revealed solitary wave velocity of about 60 km/s is consistent with the results of electric field interferometry (SM), which is another technique for estimating wave velocities (for example, Graham et al., 2016; Steinvall et al., 2022). Using solitary wave velocity V s = 60 km/s, we compute the electrostatic potential φ = ∫E L V dt and also translate temporal solitary wave profiles into spatial ones.…”
Section: Data and Case Studiessupporting
confidence: 80%
“…The use of the time delay between V 1 and − V 2 provides the speed estimate of only a few km/s, but these voltage signals were poorly correlated, and the solitary wave was barely propagating along this antenna ( L 12 ≈ − 0.01), which makes the speed estimate highly uncertain (Wang et al., 2021). The revealed solitary wave velocity of about 60 km/s is consistent with the results of electric field interferometry (SM), which is another technique for estimating wave velocities (for example, Graham et al., 2016; Steinvall et al., 2022). Using solitary wave velocity V s = 60 km/s, we compute the electrostatic potential φ = ∫E L V dt and also translate temporal solitary wave profiles into spatial ones.…”
Section: Data and Case Studiessupporting
confidence: 80%
“…In order to determine the electric potential from trueE $\vec{E}$ of the ESW, the propagation direction must be known. Single‐spacecraft timing (Steinvall et al., 2022) fails, since the magnetic field (and hence the wave propagation direction) is mainly along the shorter axial probes, resulting in an unmeasurable time lag. The ESWs are not observed by all four spacecraft, so we cannot use multi‐spacecraft timing to determine their velocity.…”
Section: Observationsmentioning
confidence: 99%
“…Unfortunately, the E80 interferometry technique is restricted to the spin plane, so we cannot use it to get the axial component of the wave vector. Other quantities can be timed in the axial direction, such as the potential measured at probes 5 and 6, but such timing is often unreliable (Steinvall et al., 2022).…”
Section: D Wave Vector Determination Using Spin‐plane Interferometrymentioning
confidence: 99%
“…For electrostatic waves measured by MMS, one can apply interferometry on both the probe potentials or electric fields. Using synthetic data, Steinvall et al (2022) found that one particular electric field configuration, what they call "diagonal electric field" and what we will call E80 electric field, is the most reliable quantity to apply interferometry on. In order to explain the E80 interferometry, we show in Figure 4 a schematic of MMS in the spin plane, using probes 2 and 4 we calculate the electric field E 42 , and using probes 3 and 1 we calculate the electric field E 13 .…”
Section: Spin-plane Wave Vector Determinationmentioning
confidence: 99%